HISTORY OF THE ENTRY OF ISLAM IN THE MUSLIM MINORITY AREA OF TANA TORAJA - Tahir, Qaharuddin; Alang, Sattu; Said, Nurhidayat Muhammad; Halik, Abd. (Program Pascasarjana, UIN Alauddin Makassar, 2021)
Tana Toraja is known as the only district in South Sulawesi with a Muslim minority population. This research discusses the early history and route of entry of Islam in Tana Toraja. This research is a qualitative research, with a phenomenological approach in the context of da'wah, communication and history. Data collection was carried out by observation, interviews and literature review. Data analysis techniques were carried out, referring to the data analysis principles proposed by Miles and Huberman. Which offers an interactive model analysis system, which consists of three components, namely data reduction, data display, and drawing and verifying conclusions. The results showed that the entry of Islam in Tana Toraja began with the interaction of local people with traders from Bugis Luwu, Bone and Sidenreng, then followed by the Islamization of two Toraja nobles, namely Puang Sondong in Batualu and Rangga in Madandan.